Geometry Exploration for the Development of Ethnomathematics Worksheet Based on the Ornament of Jingah River Jami Mosque - Suryaningsih, Yuni; Fajriah, Noor; Kamid, Kamid (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Lack of availability of culturally oriented worksheets around students to improve the character of loving the motherland. The Merdeka Curriculum allows educators to develop teaching materials adapted to the characteristics of each region. This study aims to establish a worksheet with ethnomathematics exploration of the ornaments of the Jingah River Jami Mosque. The research method used is the Plomp model development method which consists of four stages, namely: (1) initial investigation; (2) designs; (3) construction; and (4) test, evaluation, and revision—methods of data collection, namely the method of observation, interviews, and questionnaires. The data analysis technique used is descriptive qualitative and descriptive quantitative. The research subjects included experts as validators, and 7th-grade junior high school students on a limited basis. The results of the validator's assessment were 4,77, the results of the restricted group trials were 80,00%. So the ethnomathematics-based student worksheets for the ornament of the Jingah River Jami mosque are obtained, which are valid, and practical.